2022
DOI: 10.1186/s12931-022-02097-4
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization reveals sputum supernatant as a valuable alternative liquid biopsy for genome profiling in advanced non-small cell lung cancer

Abstract: Background Sputum biopsies offer unique advantages such as non-invasiveness and convenient collection. The one investigation so far on sputum for genome profiling in advanced non-small cell lung cancer (aNSCLC) suggested promising performance. However, it remains undefined whether clinicohistologic characteristics were associated with performance and how this knowledge could help guide choice of liquid biopsy. Methods Targeted sequencing with a 520… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…Out of 40 eligible papers, 1 was excluded from our meta-analysis ( Xie et al, 2022 ) since only TP and FN were reported in published data. The diagnostic accuracy of cfDNA analysis for the detection of KRAS mutations in NSCLC, compared with tumor tissue was shown in the Forest Plot for 39 studies, including 2,666 NSCLC patients.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 40 eligible papers, 1 was excluded from our meta-analysis ( Xie et al, 2022 ) since only TP and FN were reported in published data. The diagnostic accuracy of cfDNA analysis for the detection of KRAS mutations in NSCLC, compared with tumor tissue was shown in the Forest Plot for 39 studies, including 2,666 NSCLC patients.…”
Section: Resultsmentioning
confidence: 99%
“…This study was IRB approved and conducted in accordance with the ethical guidelines including Declaration of Helsinki and US Common Rule. by the Clinical Laboratory Improvement Amendments, according to optimized protocols as described previously (22,23). NGS library construction required a minimum of 30 ng of DNA.…”
Section: Patientsmentioning
confidence: 99%
“…Sequence data were analyzed using the Burning Rock analysis system as previously described (22,23,26). Briefly, sequence data were mapped to the reference human genome (hg19).…”
Section: Sequence Data Analysismentioning
confidence: 99%
“…Sendo assim, o Câncer de Pulmão de Células Não Pequenas (CPCNP), por ser um dos principais tipos que podem afetar fumantes e não fumantes, está mais relacionado com fatores genéticos, tendo como via comum de todos os cânceres as alterações nuclear e enzimática, dois agentes cruciais para o ciclo celular normal (AIRES; GUEDES, 2018;YIN et al, 2021). complexas e diferentes, sendo assim, a IHQ é capaz de classificar os tipos de neoplasias de modo essencial para o tratamento, prognóstico e recidiva, com auxílio dos marcadores tumorais (INAMURA, 2018;RAJGURU et al, 2020;XIE et al, 2022;YANG et al, 2022).…”
Section: De Acordo Com O Estudo Deunclassified